Construction of a highly-effective/sustainable corrosion protective composite nanofilm based on Aminotris(methylphosphonic acid) and trivalent cerium ions on mild steel against chloride solution. (20th November 2020) - Dehghani, Ali; Ramezanzadeh, Bahram; Poshtiban, Fatemeh; Bahlakeh, Ghasem
Highlights: ATMP:Ce mixtures were used as organic–inorganic inhibitors for steel substance. The EIS analysis demonstrated 93% inhibition degree using 400:400 ppm of ATMP:Ce. Inhibitive-film based on ATMP-Ce (III)/CeO2 /Ce(OH)3 complexes formed on the steel. ATMP:Ce(III) mixture reduced the steel aggression by a mixed type mechanism. Abstract: In this study, Aminotris(methylphosphonic acid) (ATMP) was combined with rare-earth cerium (III) salt at different ratios to make an organic-ceramic complex anti-corrosive nanofilm for the mild steel (MS) surface to reduce its aggression in saline media. The ATMP:Ce (III) chelated compounds chemistry was discovered by Fourier-transform infrared spectroscopy (FT-IR) and ultraviolet–visible (UV–Vis) spectroscopies. The electrochemical impedance spectroscopy (EIS) and Tafel analysis demonstrated 93% protection capacity via mixed inhibition mechanism by applying 400:400 ppm of ATMP:Ce during 96 h of immersion of the metal sample. Achievements from the scanning electron microscope (SEM) micrographs and energy-dispersive X-ray spectroscopy (EDS) diagrams disclosed the formation of a sufficient inhibitive film composed of ATMP-Ce (III) and ATMP-Fe (II) complexes on the MS substrate. The final grazing incidence X-ray diffraction (GIXRD) patterns evidenced that the enhancement of 400:400 ppm ATMP:Ce (III) in a saline environment resulted in the ATMP:Ce complex nanofilm construction over the active sites of MS.